2013
DOI: 10.3758/s13420-012-0101-7
|View full text |Cite
|
Sign up to set email alerts
|

Analogical reasoning in baboons (Papio papio): Flexible reencoding of the source relation depending on the target relation

Abstract: Analogical reasoning is a cornerstone of human cognition, but the extent and limits of analogical reasoning in animals remains unclear. Recent studies have demonstrated that apes and monkeys can match relations with relations, suggesting that these species have the basic abilities for analogical reasoning. However, analogical reasoning in humans entails two additional cognitive processes that remain unexplored in animals. These include the ability to (1) flexibly reencode the relations instantiated by the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Critically, no items in the correct test pair physically match items in the sample pair, thus demanding that only relational sameness or differentness is available to support accurate choice responding. Initial evidence suggested that only humans and apes can successfully learn RMTS with pairs of sample and test items [4][5][6][7]; however, monkeys have subsequently done so [8][9][10][11][12]. Here, we report that crows too exhibit relational matching behavior.…”
mentioning
confidence: 51%
“…Critically, no items in the correct test pair physically match items in the sample pair, thus demanding that only relational sameness or differentness is available to support accurate choice responding. Initial evidence suggested that only humans and apes can successfully learn RMTS with pairs of sample and test items [4][5][6][7]; however, monkeys have subsequently done so [8][9][10][11][12]. Here, we report that crows too exhibit relational matching behavior.…”
mentioning
confidence: 51%
“…We also note that, although the majority of studies identified in our review, unsurprisingly, tested aspects of primate social cognition (e.g., social learning, cooperation, competition, and communication), this was not exclusively so. Highlighting that a social test setting does not prohibit the testing of non-social cognition, our review revealed tests of, for example, analogical reasoning ( Fagot & Maugard, 2013 ), memory ( Fagot & de Lillo, 2011 ; Maugard, Marzouki & Fagot, 2013 ), visual perception ( Cheries et al, 2006 ), numerical understanding ( Hauser, Carey & Hauser, 2000 ), and personality ( Carter et al, 2012 ; Neumann et al, 2013 ), although we note the inherent complexity of teasing apart “social” from “non-social” cognition (c.f. Seyfarth & Cheney, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence of analogical reasoning in animals came from studies of great apes trained on relational matching-to-sample (RMTS) and similar tasks (Gillan et al 1981;Oden et al 2001;Premack 1983;Thompson et al 1997; Thompson and Oden 2000;Vonk 2003). Later work found that not only apes, but also monkeys can match relations between relations, suggesting that these primates too have the basic cognitive capacities for analogical reasoning (Bovet and Vauclair 2001;Fagot et al 2001;Fagot and Maugard 2013;Fagot and Thompson 2011;Fagot and Parron 2010;Flemming et al 2013;Truppa et al 2010Truppa et al , 2011.…”
Section: Introductionmentioning
confidence: 99%